THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING (CTL) ON LEARNING OUTCOMES ON PLANT DEVELOPMENT MATERIALS OF CLASS VI STUDENTS OF SDN BALEATU REGENCY REALLY FUN - Nurhayati, Nurhayati; Sulaiman, Sulaiman; Safiah, Intan (Universitas Syiah Kuala, 2024)
The Contextual Teaching and Learning model is a learning model that connects the material taught with real world life which is very suitable for science learning. However, in reality there are still many students who do not understand science learning in the material of plant reproduction because learning is only focused on the material. . So this research aims to analyze the influence of the Contextual Teaching and Learning (CTL) model on learning outcomes in plant breeding material for class VI students at SDN Baleatu. This research uses a Quasi Experimental quantitative approach with a Nonequivalent Control Group Design. The population in this study were all class VI students at SD Negeri Baleatu with a total of 63 students. The sample in this study was class VIa with a total of 35 people and class VIb with a total of 28 people, where class VIa was the experimental class and class VIb was the control class. Data collection techniques use tests in the form of pretest and posttest. The data analysis technique in this research uses SPSS software version 25 and hypothesis testing paired sample T-test. The results of hypothesis testing using the paired sample T-test obtained a significance value (2-tailed) of 0.000 0.05. So the decision making criteria are Ha accepted and H0 rejected. Based on this, it can be concluded that there is a significant influence from the application of the Contextual Teaching and Learning (CTL) model in Bener Meriah district.